Morphometric study of tortuous seminiferous tubules of testes of rats of different ages - Pastukhova , V.A.; Lukyantseva , G.V.; Krasnova , S.P. (Морфологія / Morphologia / Morfologìâ, 2024)
The relevance of the study of the morphometry of the seminiferous tubules of the testicles in different age periods is determined by the fact that knowledge about the evolution of the seminiferous glands in ontogenesis has clinical significance and is necessary for a correct understanding of the etiology and pathogenesis of diseases of the male reproductive system. The goal is to establish the age-related regularities of the structure of convoluted seminiferous tubules of rat testicles. Methods. The study was conducted on sexually immature, sexually mature and old white rats. Morphometric calculations of rat convoluted tubules were performed on thin sections of testes stained with hematoxylin-eosin. The diameter of the tubule, the thickness of the epithelium, as well as the coefficient reflecting the percentage of the tubule filled with epithelium were calculated. Results. The data of morphometric calculations showed that the diameter of convoluted seminiferous tubules of sexually immature rats is more than twice as thin as compared to sexually mature animals and is 198.9+10.3 μm versus 495.2+30.15 μm. Also characteristic is the twice smaller thickness of the spermatogenic epithelium, which amounts to 98.4+9.0 μm, which almost completely fills the lumen of the tubule by 99+9%. The presented data reflect the absence of all stages of spermatogenesis in sexually immature rats, as evidenced by the qualitative composition of the tubule epithelium: they lack mature spermatids and spermatozoa. With the onset of puberty, both the diameter of the convoluted tubules and the thickness of the spermatogenic epithelium increase, which are 495.2+41.15 and 187.1+13.5 μm, respectively. This is due to the beginning of full-fledged spermatogenesis and the presence of all classes of spermatogenic cells. In adult animals, the lumen of the convoluted tubule appears, which provides its drainage function, thanks to which mature spermatozoa are excreted. Cells of the spermatogenic epithelium in sexually mature animals occupy 76+4% of the thickness of the entire tubule. At the same time, a significant variation in the diameter of the convoluted tubules was noted. Small tubules were 300 to 365 microns in size. The main population consisted of tubules with a diameter of 420 to 540 μm. Large tubules accounted for 27%. The described heterogeneity of tubule thickness reflects their spermatogenic activity, since the diameter of convoluted tubules is directly proportional to the intensity of spermatogenesis. In old rats, there is a significant decrease in the diameter of the convoluted tubules and the thickness of the spermatogenic epithelium, and the percentage of tubule filling, which is 55+8%, is significantly reduced. These data indicate inhibition of the intensity of spermatogenesis in old animals. Conclusion. The obtained data confirm the qualitative analysis of the morpho-functional state of rat testicles in the age aspect and reflect the sequence of changes in the pre-spermatogenic stage in sexually immature animals, the stage of active spermatogenesis in sexually mature animals and its inhibition in old rats.